Estimation of human induced disturbance of the environment associated with 2002, 2008 and 2013 land use/cover patterns in Mexico. (January 2016) - Roth, Deborah; Moreno-Sanchez, Rafael; Torres-Rojo, Juan Manuel; Moreno-Sanchez, Francisco
Abstract: Land use/cover types have an associated level of human induced disturbance of the environment. Previous studies in Mexico document the extent of land use/cover types and their changes over time. This information is important but not sufficient to support land use planning and environmental conservation decisions. This article explores the informational value of generating a numerical quantification of the level of human induced disturbance of the environment associated with land use/cover classes and their patterns at the national and state levels in Mexico. Estimates for land use/cover patterns existing in 2002, 2008 and 2013 are created. A disturbance scale created in a previous study was adapted and calibrated for 14 broad land use/cover types through domain expert opinions. The results indicate that the disturbance of the environment is increasing at the national level, but at a significantly slower rate between 2002 and 2008 (1.9%) and 2008–2013 (0.8%). Six states report a decrease in total environmental disturbance. A land use/cover transition analysis conducted for these states indicates a large proportion of transitions from anthropogenic land use/covers to natural ones. Highlights: Assessment of environmental disturbance associated with land use/cover patterns. Three dates were examined 2002, 2008 and 2013 at the state and national level. Disturbance of the environment is increasing, but at a decreasing rate. Six states out of 32 show decrease in total environmental disturbance. Disturbance information complements land use/cover change information.